Implementation Of Project-Based Learning To Support Merdeka Curriculum In Raudhatul Atfhal Dau : Implementasi Pembelajaran Berbasis Proyek untuk Mendukung Kurikulum Merdeka di Raudhatul Atfhal Dau. - Dewi*, Mutiara; Sulistiani, Ika Ratih; Azizah, Afriska Nur; Yuliana, Aris (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Competencies that must be mastered by teachers include being able to apply learning models that are in accordance with the development of the educational curriculum. One of the learning models that supports the realization of kurikulum merdeka is a project-based learning model. Community service activities were carried out by involving Raudhatul Atfhal teachers of DAU District, stakeholders, and a team of experts as resource persons. The community service method used is the Community Based Research (CBR) method. The tools used in this activity are the RRA (Rapid Rural Appraisal) technique. The stages in this service activity refer to the CBR stages and are guided by the RRA technique. The activity partners are RA teachers in DAU District, but for the pilloting project, the assistance is carried out on 21 representative teachers from all RAs in DAU District. The results of service activities showed an increase in understanding that was seen in the results of the initial survey, as many as 5 teachers (23.8%) expressed their agreement, and 7 teachers (33.3%) stated that they quite agreed that the implementation of the PjBL model must incur large costs and can only be applied optimally by institutions that have adequate facilities. Meanwhile, the results of the final survey showed an increase in understanding, especially related to the technical understanding of PjBL in terms of utilizing the surrounding environment to save the cost of toys. In fact, the assessment related to the benefits of the information presented showed that 90% of the participants strongly agreed with the average answer reaching 4.9. These results can be interpreted as participants feeling a lot of benefits to the implementation of activities. Teachers who originally considered the merdeka curriculum with the PjBL learning model were complicated activities.